The Reason for the Length of Speech in Arabic Syntax: A Study of Concept and Usage - ALbderat, Basem Younes; AlMasarwah, Jazaa Mohammad (Dirasat: Human and Social Sciences, 2024)
Objective: This paper aims to elucidate the phenomenon of ‘length of speech’, gauge its use by grammarians in their explanations, understand why they rely on it, and identify the critical issues predominantly elucidated by this phenomenon. Methods: The study adopted an analytical descriptive approach to describe and explain the linguistic phenomenon. It compiled most grammatical issues explained by grammarians using the ‘length of speech’ phenomenon from various grammar books. These issues were then categorized based on the reasons leading to the length of speech, and the grammarians making use of this phenomenon were highlighted. Conclusion: The study demonstrates that 'length of speech' is a grammatical phenomenon often relied upon by grammarians to explain language structure. This depends on the count of morphemes constituting a sentence. Its most notable manifestations in the grammatical lessons are the separation of morphemes, the absence of a preceding word, and the use of a word for two things to attain its syntax and meaning. Recommendations: The research concluded that the most pronounced rules based on the reason for the length of speech include deletion (which happens most frequently), a shift in inflection from heavier to lighter, reiteration of an advanced word so it's not forgotten, or a weakness in the grammatical factor. The study deduced that 'length of speech' as a reason for grammarians is predominantly represented in the infinitive, the relative noun with its connection, the conditional sentence, and the structure of a nominal sentence following 'law la'. This study recommends emphasizing the reason for 'length of speech' conspicuously when studying or teaching linguistic phenomena.